The balance between a usable and emotional product design – a comparison of different methods for prioritising relevant influencing factors - van Remmen, Judith Sophie; Horber, Dennis; Händel, Jonas; Miehling, Jörg; Wartzack, Sandro (DESIGN 2024, 2024)
Designing an equally usable and emotionally appealing product remains a challenge for product developers, not least due to conflicting goals. Product developers need to constantly map the affective user requirements to the product, whereby the requirements for the emotional and usable product design often cannot be equally addressed. The systematic approach presented can help product developers in conflicting decision-making situations to represent these affective user requirements by selecting and prioritising context-relevant influencing factors using multi-criteria decision-making methods.<br
Keywords: user-centred design; emotional engineering; user experience; decision making